Innovation in Boundary-Spanning Technology M&A: A Fuzzy-Set Analysis of Diversity Dynamics - Qi, Meng; Li, Xiaoyi; Wang, Wanqiu (Frontiers in Psychology, 2022)
The growing literature on organizational innovation has drawn attention from net effect and contingent effect of diversity-related factors in the context of top management teams (TMTs) to their complementarity and interaction in the form of configurations. In post-boundary-spanning technology mergers & acquisitions (M&A), the integration between multi-boundary knowledge and resources necessitates effective communication and cooperation within TMTs that display heterogeneous attributes. Therefore, this study integrates two popular theoretical perspectives from the diversity literature (social categorization perspectives and information/decision-making perspectives) in order to explore the configurational patterns of factors stimulating innovation in boundary-spanning technology M&A (BTM&A). In accordance with this theoretical objective, this study adopts fuzzy-set qualitative comparative analysis for the purpose of examining the complex combinations of five antecedent conditions (functional experience diversity, boundary-spanning experience diversity, faultline strength, number of subgroups, and subgroup balance) based on a BTM&A sample of firms in the Chinese A-share market during the period 2007-2018. Findings from this analysis indicates four configurations of diversity-related factors (the dominated multiple diversities; the non-aligned multiple diversities; the balanced similarity; and the aligned single diversity) which lead to superior innovation in BTM&A. This study fills a gap in the literature vis-à-vis the causes of innovation in BTM&A and provides novel insights for management practitioners to take appropriate countermeasures with regard to TMT diversity.